Forage lignocellulose is an important factor in driving the seasonal dynamics of rumen anaerobic fungi in grazing yak and cattle - Zeyi Liang; Jianbo Zhang; Ahmad, A.A.; Han Jianlin; Gharechahi, J.; Mei Du; Juanshan Zheng; Peng Wang; Ping Yan; Salekdeh, G.H.; Xuezhi Ding (American Society for Microbiology, 2023)
Anaerobic fungi (AF) inhabit the gastrointestinal tract of ruminants and play an important role in the degradation of fiber feed. However, limited knowledge is available on seasonal dynamics and inter-species differences in rumen AF community in yak and cattle under natural grazing systems. Using the random forests model, the null model, and structural equation model, we investigated the seasonal dynamics and key driving factors of fiber-associated rumen AF in grazing yak and cattle throughout the year on the Qinghai-Tibet Plateau (QTP). We found that the richness and diversity of rumen AF of grazing yak and cattle in cold season were significantly higher than those in warm season (P < 0.05). We identified 12 rumen AF genera, among which, Cyllamyces, and Orpinomyces were predominant in the rumen of both grazing yak and cattle. LEfSe and random forest analysis showed that Feramyces, Tahromyces, and Buwchfawromyces were important seasonal indicator of rumen AF in grazing yak (P < 0.05), and Caecomyces, Cyllamyces, and Piromyces in grazing cattle (P < 0.05). Null model analysis revealed that the dynamic changes of rumen AF community structure were mainly affected by deterministic factors. Notably, mantel test and structural equation model revealed that forage physical-chemical properties, including dry matter (DM), neutral detergent fiber (NDF), and hemicellulose contents (HC) were the key factors driving the seasonal variations of the rumen AF community (P < 0.05). The results revealed that forage lignocellulose was probably an important factor affecting the seasonal dynamics and inter-species differences of the rumen AF community under natural grazing conditions.